Paeonia arietina and Paeonia kesrounansis bioactive constituents: NMR, LC-DAD-MS fingerprinting and in vitro assays - DOĞAN, AHMET; EMRE, GİZEM (ELSEVIER SCIENCE BV, 2019)
Paeonia species have been valued for their ethnomedicinal uses in various countries and received much interest among the scientific community for their therapeutic properties, including anti-microbial, anti-inflammatory, anti-cancer, nephroprotective and hepatoprotective effects. The multiple phytother-apeutical applications of Paeonia species inspired us to establish the phytochemical fingerprint and to evaluate the biological properties of ethyl acetate, methanol, and aqueous extracts from the roots and aerial parts of two Paeonia species (P. arietina G. Anderson and P. kesrounansis Thiebaut). Phytoconstituents of P. arietina and P. kesrounansis extracts were analyzed using 1D and 2D NMR and LC-DAD-ESI-MS. The total content of phenolics (TPC) and flavonoids (TFC) in the extracts was also evaluated. The antioxidant activity was profiled using DPPH, ABTS, CUPRAC, FRAP, phosphomolybdenum, and metal chelation assays. Enzyme inhibitory properties were evaluated against acetylcholinesterase (AChE), butyrylcholinesterase (BChE), tyrosinase, alpha-amylase, and alpha-glucosidase. Phytochemical analysis of P. arietina and P. kesrounansis extracts showed the presence of galloyl esters of sugars, galloyl monoterpenes, and glycosylated flavonoids. The three solvent extracts presented different behavior in the bioassays. The highest antioxidant activity, tyrosinase and AChE inhibition were observed for the methanolic extract of the aerial parts of P. kesrounansis. In addition, the ethyl acetate extracts of the aerial parts of both plants were the most effective inhibitors of alpha-amylase. The highest BChE inhibition was observed for root methanolic extract of P. kesrounansis while the root ethyl acetate extract of P. arietina exerted the strongest inhibition of alpha-glucosidase. Methanol extract of P. kesrounansis aerial parts presented the highest TPC, while TFC was greatest in the corresponding extract of P. arietina. Our findings can be considered as a starting point for future studies to further validate the effectiveness and safety profiles of these plants in folk medicine. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Paeonia arietina; Paeonia kesrounansis; Antioxidant; Cholinesterase; Tyrosinase; alpha-Glucosidase; alpha-Amylase; MEDICINAL-PLANTS; ANTIOXIDANT; LACTIFLORA; GLYCOSIDES; EMODI